Evaluation of Android and Apple Store Depression Applications Based on Mobile Application Rating Scale. - Martín-Martín, Jaime; Muro Culebras, Antonio Luis; Roldán-Jiménez, Cristina; Escriche-Escuder, Adrián; De Torres García, Irene; González-Sánchez, Manuel; Ruiz-Muñoz, María; Mayoral Cleries, Fermín; Biró, Attila; Tang, Wen; Nikolova, Borjanka; Salvatore, Alfredo; et al. (MDPI, 2021)
There are a large number of mobile applications that allow the monitoring of health status. The quality of the applications is only evaluated by users and not by standard criteria. This study aimed to examine depression-related applications in major mobile application stores and to analyze them using the rating scale tool Mobile Application Rating Scale (MARS). A search of digital applications for the control of symptoms and behavioral changes in depression was carried out in the two reference mobile operating systems, Apple (App Store) and Android (Play Store), by means of two reviewers with a blind methodology between September and October 2019 in stores from Spain and the United Kingdom. Eighteen applications from the Android Play Store and twelve from the App Store were included in this study. The quality of the applications was evaluated using the MARS scale from 1 (inadequate) to 5 (excellent). The average score of the applications based on the MARS was 3.67 ± 0.53. The sections with the highest scores were "Functionality" (4.51) and "Esthetics" (3.98) and the lowest "Application Subjective quality" (2.86) and "Information" (3.08). Mobile Health applications for the treatment of depression have great potential to influence the health status of users; however, applications come to the digital market without health control.
Keywords: Aplicaciones para móviles; Salud - Sistemas de comunicación; Promoción de la salud; Depression; Exercise; Mobile app rating scale; Mobile application; Mobile health; Smartphone; Telemedicine